Meningkatkan Keterampilan Anggah-Ungguhing Bahasa Bali Melalui Metode Kooperatif Tipe Jigsaw Berbantuan Flash Card Pada Siswa Kelas V SDK Karya Singaraja - Putu Suwid Nyana; I Made Sutama; I Putu Mas Dewantara; Kadek Wirahyuni (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
The low learning outcomes of students in the Balinese language subject on the Balinese language anggah-ungguhingmaterial are a challenge for Balinese language teachers, especially at SDK Karya Singaraja. Therefore, learning innovations are needed. This study aims to analyze: (1) the application of the jigsaw type cooperative model assisted by flash cards in improving the Balinese language anggah-ungguhingability of class V students at SDK Karya Singaraja. The type of research conducted is classroom action research (CAR). (2) the learning outcomes of students' anggah-ungguhingthrough the application of the jigsaw type cooperative model assisted by flash cards in class V students at SDK Karya Singaraja. (3) students' opinions about the application of the jigsaw type cooperative model assisted by flash cards in improving the Balinese language anggah-ungguhingability. The subjects of this study were 28 class V students. The data collection methods used were tests, interviews, and observation sheets. Data analysis in classroom action research involves observation and research of each step from preparation to final activities. This classroom research was conducted in two cycles which included four stages, namely: planning, implementation, observation, and reflection. The results of this data analysis will be used to assess students' Balinese language anggah-ungguhingabilities. The results of the study are as follows: (1) the implementation of learning in accordance with the planning consists of an opening, core, and with two learning cycles. (2) the learning outcomes of anggah-ungguhingbahasa Balinese assisted by flash cards for grade V students increased in cycle I, namely 73.35 and cycle II, namely 80.71, and (3) students' opinions about the implementation of the jigsaw type cooperative model assisted by flash cards in learning anggah-ungguhingbahasa Balinese in cycle I, namely 21.93 and cycle II, namely 24.10, are in the very good category. This shows that there are very significant implications for students, namely creating active and collaborative learning where students are able to work together and be responsible for each other. In addition, the implementation of the jigsaw type cooperative model can develop social and emotional skills that can improve student learning outcomes.